2013
DOI: 10.1007/s40266-012-0046-8
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Use and Frailty among Community-Dwelling Older People

Abstract: Frailty was associated with a higher prevalence of analgesic use. As frail older people may be more susceptible to adverse events, careful selection of analgesics is warranted. Clinicians should pay more attention to pain management to ensure adequate pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…We identified seven studies which reported pain outcomes in older people with frailty (table 1). One study was conducted in Canada 11,17 , one in Australia 18,19 , one in Finland 20 , two in Taiwan 13,21 , and two in Brazil 22,23 . The mean age of participants ranged from 71 years to 82 years (see table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We identified seven studies which reported pain outcomes in older people with frailty (table 1). One study was conducted in Canada 11,17 , one in Australia 18,19 , one in Finland 20 , two in Taiwan 13,21 , and two in Brazil 22,23 . The mean age of participants ranged from 71 years to 82 years (see table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Chang et al 21 reported the presence of pain history but did not report the specific measure. The Geriatric Multidisciplinary Strategy for the Good Care of the Elderly (GeMS) study investigated the presence and severity of musculoskeletal pain, and chronicity 20 . The frailty in the Brazilian elderly (FIBRA) study 22 used the Western Ontario and McMaster Universities Questionnaire (WOMAC).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations